Does Technology Bring Happiness? Evidence From Turkey - Hamzaoğlu, Nazife Merve; Yolusever, Aras (My University, 2022)
As the ultimate goal of life, happiness has remained the main focus in human history. Happiness economics has been recently one of the trending topics among researchers. As a main driver in the economic growth, technology is crucial in welfare level of economic agents. It is evident that daily life has been becoming more digitalized and technological advances directly and indirectly affect the life standards. In this sense, happiness of human being is also directly and indirectly affected by technological changes and they have an impact on life standards and daily routines. In this study, we aim to see the impact of technology on happiness in Turkey. Since there are few studies on this topic examining Turkey, we want to reveal the impact of technology on happiness level among Turkish citizens. To do so, we collected the data from World Values Survey (2017-2021) and analyzed the data collected from Turkey. Our results show that technological changes and scientific innovations do not have significant impacts on happiness in Turkey, but financial indicators do.
Keywords: Technology; Teknoloji